2012
DOI: 10.1074/jbc.m111.327387
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Mycobacteria to Cell Wall-inhibitory Drugs Decreases Production of Arabinoglycerolipid Related to Mycolyl-arabinogalactan-peptidoglycan Metabolism

Abstract: Background: Mycolyl-arabinogalactan-peptidoglycan (mAGP) represents the hallmark of the mycobacterial cell envelope and the target of several antitubercular drugs. Results: Loss of a glycolipid structurally analogous to the terminal portion of mAGP correlates with drug treatment in mycobacteria. Conclusion:This work establishes the versatility of arabinoglycerolipids in M. tuberculosis. Significance: Further work will define the importance of the metabolic relationship between the two components in cell wall r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…Structure of Mycobacterium marinum DMAG-We have recently shown that several slow-growing mycobacterial species, including M. bovis BCG, M. tuberculosis, and Mma produce an apolar cell wall-associated glycolipid whose synthesis was altered by several anti-tubercular drugs inhibiting arabinogalactan or mycolic acid biosynthesis (33). Structural elucidation of this product in M. bovis…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Structure of Mycobacterium marinum DMAG-We have recently shown that several slow-growing mycobacterial species, including M. bovis BCG, M. tuberculosis, and Mma produce an apolar cell wall-associated glycolipid whose synthesis was altered by several anti-tubercular drugs inhibiting arabinogalactan or mycolic acid biosynthesis (33). Structural elucidation of this product in M. bovis…”
Section: Resultsmentioning
confidence: 99%
“…Mma_DMAG was then purified by two successive rounds of absorption chromatography, as reported earlier (33). Briefly, the crude apolar extract was dissolved in chloroform and fractionated by silica gel column flash chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations